Fusarium graminearum control using the leaves alcoholic extracts of the Cassia spp, Salvia officinalis and Achillea millefolium - Nadia Mahmoud (College of Education for Pure Sciences, 2012)
ABSTRACT In this study the effect of alcoholic leaves extracts of Cassia spp, Salvia officinalis and Achillea millefolium was tested on the growth of the fungus Fusarium graminearum which was isolated from rice. Four concentration (5,10,15,20 mg/ml) for each plant were used. it was noticed that the inhibition effect of these extracts increase with increasing the concentration of them Prcentage of Cassia spp, Salvia officinalis, Achillea millefolium were (35.7, 100, 100%) respectively at the concentration 20 mg/ml. These results were compared with bioresistor Trichoderma harzianum, Trichoderma viride since they gives high antagonistic efficiency reached to 100 % Therefore we advice to use these plant extracts instead of chemical substance (fungicide), Because they are cheap, safety in use and don't have any poisons effect on plant, animal, human and environment in addition the achieving of these extracts was very easy and available in nature.